Hitler and the Abortion Debate. Issue 1 (June 2016) - Steinem, Gloria
As anti-abortion movement surges worldwide in sync with the rise of right wing politics, seeking to thwart feminists and the right to self, this article shows that this is not a new phenomenon. The author looks at Germany during the time of Hitler to deliberate upon the tension between reproductive choice as a right of an individual and the right of the state to impose. She focuses on how the anti-abortion movement is not just about the right to abortion but veils the right wing leadership's attempt to legitimize a militaristic, religious and 'back-to-basics' kind of patriotism; and a patriarchal state. She also engages with the concept of fear that is associated with the anti-abortion movement, particularly with a state endorsed anti-abortion movement, a fear of declining birth rate (especially that of the majority population's), a fear of declining 'racial purity'—and articulates how this whole idea should be understood as a form of injustice to both men and women.